Coming home without supplies: Impact of household needs on bribe involvement and gender gaps - Edward Asiedu (Georg-August-Universität Göttingen, Research Training Group (RTG) 1666 - GlobalFood, 2016)
Using a unique data on sub-Saharan Africa, we show that even though in absolute terms men pay more bribes, in relative terms, women are more likely to be involved in bribery or do favors that benefit the household. Additionally, running country specific regressions shows that for 65% of the countries gender differences when household needs are at stake disappear. These results underscore the importance of household needs to the woman, and that the effect of gender on corruption may well be context specific.
Keywords: D1; J16; H10; K42; 330; service delivery; gender; bribe-involvement; household needs; Africa